Penetapan Fosfor Tersedia pada Sampel Tanah Menggunakan Metode Olsen & Bray I - Nur Kholifah, Azzahra; Pawestri, Niken; Utami, Maisari (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2025)
Quantitative analysis was conducted on seven soil samples to determine available phosphorus (P), an essential macronutrient for plant growth and development. This study aimed to compare the effectiveness of two extraction methods, Olsen and Bray I, in measuring phosphorus availability in soils with different chemical characteristics, as well as to provide an overview of soil fertility levels based on the obtained results. The available P content was measured using the Olsen & Bray I methods with a single-beam UV-Visible spectrophotometer. Four soil samples (TH.2278, TH.2279, TH.2280, and TH.2281) were analyzed using the Olsen method, while three samples (TH.2267, TH.2268, and TH.2269) were analyzed using the Bray I method. Based on the Olsen method, samples TH.2278 and TH.2279 contained 34.8270 ppm and 50.5795 ppm P₂O₅, respectively, both classified as very high. In contrast, sample TH.2280 showed a concentration of 3.9325 ppm (very low category), and sample TH.2281 had 8.9920 ppm (low category). Using the Bray I method, sample TH.2267 contained 39.9138 ppm P₂O₅ (very high category), while TH.2268 and TH.2269 contained 1.7534 ppm and 5.3627 ppm, categorized as very low and low, respectively. Overall, three samples (TH.2278, TH.2279, and TH.2267) exhibited very high levels of available phosphorus, while samples TH.2280, TH.2281, TH.2268, and TH.2269 fell within the low to very low categories. These findings indicate that phosphorus availability is strongly influenced by soil chemical conditions, with the Olsen method being more suitable for neutral to alkaline soils and the Bray I method being more responsive to acidic soils. For soils with very high phosphorus levels, phosphate fertilization should be temporarily discontinued to prevent nutrient imbalance and environmental risks. Conversely, soils with low phosphorus levels require regular monitoring and periodic phosphate fertilization to maintain adequate soil fertility.